Answers

2015-04-06T00:09:40+05:30
Let amount(A) = 3x Let sum(P) = x =>A = P (1 + R/100)^t =>3x = x (1 + R/100)^5 =>3 = (1 + R/100)^5 A = 27x P = x =>27x = x (1 + R/100)^t =>27 = (1 + R/100)^t =>(3)^3 = (1 + R/100)^t =>(1 + R/100)^(3*5) = (1 + R/100)^t t = 15 years
0
2015-04-06T11:43:40+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Sum accumulated with compound interest = P (1 + r/100)⁵ = 5 P
   =>  1 + r/100 = 5¹/⁵ = 1.3797
   r/100 = 0.3797
   r = 37.97%

   in 27 years:  P (1 + 37.97/100)^n = 27 * P
         =>  n Log 1.3797  =  log 27
                   n = Log 27 / Log 1.3797 = 10.239

   in 10.239 years the money will be 27 times

1 5 1